Social Mobilisations and Corporate Accountability in Brazil: The Volkswagen Case and the Limits of Legal Settlements - Bohoslavsky, Juan Pablo Raimundo (2025)
This chapter examines the legal and political strategies designed and implemented by victims, prosecutors, civil society organizations, and trade unions in Brazil and Germany against Volkswagen do Brasil for its complicity in crimesagainst humanity perpetrated during the Brazilian dictatorial regime. These strategies gave rise to a controversial agreement, signed in 2020, between Volkswagen do Brasil and the Federal Prosecutor’s Office. We provide a framework for critically evaluating the potential and pitfalls of these strategies and analyze the process and terms of the agreement, through an actor-focused perspective that might be useful for subsequent comparative analysis.